2020
DOI: 10.1159/000505710
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contribution of Magnetic Resonance Imaging, Microelectrode Recordings, and Awake Test Stimulation in Final Lead Placement during Deep Brain Stimulation Surgery of the Subthalamic Nucleus in Parkinson’s Disease

Abstract: <b><i>Introduction:</i></b> For deep brain stimulation (DBS) surgery of the subthalamic nucleus (STN) in Parkinson’s disease (PD), many centers employ visualization of the nucleus on magnetic resonance imaging (MRI), intraoperative microelectrode recordings (MER), and test stimulation in awake patients. The value of these steps is a subject for ongoing debate. In the current study, we determined the relative contribution of MRI targeting, multitrack MER, and awake test stimulation in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Deep brain stimulation (DBS) as a therapeutic approach to movement disorders such as Parkinson disease (PD), dystonia, and tremor has always relied on neuroimaging for precise lead placement [1]. Still, to date, no generally accepted protocol for lead localization has been established, and most clinicians use imaging fusion of pre- and postoperative cranial computer tomography (CCT) and/or magnetic resonance imaging (MRI) data to confirm the lead location at the attempted site [2].…”
Section: Introductionmentioning
confidence: 99%
“…Deep brain stimulation (DBS) as a therapeutic approach to movement disorders such as Parkinson disease (PD), dystonia, and tremor has always relied on neuroimaging for precise lead placement [1]. Still, to date, no generally accepted protocol for lead localization has been established, and most clinicians use imaging fusion of pre- and postoperative cranial computer tomography (CCT) and/or magnetic resonance imaging (MRI) data to confirm the lead location at the attempted site [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several groups reported good clinical outcomes in patients with Parkinson's disease undergoing STN DBS surgery under general anesthesia [45][46][47]. In our previously mentioned 2020 study employing MRI targeting, three-channel MER, and awake test stimulation, we retrospectively determined the relative contribution of awake test stimulation in STN DBS lead placement by analyzing where final DBS leads were implanted and why these locations were chosen [37]. For final lead placement, the MRI-targeted trajectory was chosen in 39% of STNs (18% of bilaterally implanted patients), the trajectory with the longest STN MER signal in 60% of STNs (38% of bilaterally implanted patients).…”
Section: Awake Test Stimulationmentioning
confidence: 99%
“…In 2010, we reported how often each of these five MER channels was chosen for final STN DBS lead implantation: the central channel was chosen in 50% of the cases, the anterior channel in 24%, the lateral channel in 10%, the posterior channel in 10%, and the medial channel in 6% [ 35 ]. Because of these results and the finding of a systematic literature review showing that the number of MER penetrations may increase the risk of intracerebral hemorrhage [ 36 ], we reduced the number of MER channels in the years thereafter to three (MRI target, 2 mm anterior and 2 mm lateral channels) and found that 92% of final STN DBS leads were indeed implanted in one of those three channels [ 37 ]. Three-channel instead of five-channel MER thus provides sufficient accuracy to target the dorsolateral STN in the large majority of patients.…”
Section: Microelectrode Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports that suggest MER significantly improves DBS outcomes [ 80 ], and that MER fails to show any significant benefit compared to direct targeting [ 81 ]. Moreover, there remains a mismatch of around 20% in the planned target coordinate based on MRI, compared to the actual optimal location identified with MER when using 1.5 and 3 T [ 82 , 83 ]. Further, the use of intra-operative ultra-low field MRI for identification of the test leads during surgery has shown to be as effective as MER in improving post-operative motor symptoms [ 84 ].…”
Section: Current Procedures For Intra- and Post-operative Verificamentioning
confidence: 99%